The intraperitoneal ondansetron for postoperative pain management following laparoscopic cholecystectomy: A proof-of-concept, double-blind, placebo-controlled trial - Abdelaziz, Doaa; Boraii, Sherif; Cheema, Ejaz; Elnaem, Mohamed Hassan Abdelaziz; Omar, Tamer; Abdelrauof, Amr; Mansour, Noha (Elsevier, 2021)
Background Pain after laparoscopic cholecystectomy remains a major challenge. Ondansetron blocks sodium channels and may have local anesthetic properties.